Temporo-spatial distribution of stem cell markers CD146 and p75NTR during odontogenesis in mice - Aline QUEIROZ; Cibele PELISSARI; Victor Elias ARANA-CHAVEZ; Marília TRIERVEILER (University of São Paulo, 2021)
Abstract Mesenchymal and epithelial stem cells were identified in dental tissues; however, knowledge about the odontogenic stem cells is limited, and there are some questions regarding their temporo-spatial dynamics in tooth development. Objective Our study aimed to analyze the expression of the stem cell markers CD146 and p75NTR during the different stages of odontogenesis. Methodology The groups consisted of 13.5, 15.5, 17.5 days old embryos, and 14 days postnatal BALB/c mice. The expression of CD146 and p75NTR was evaluated by immunohistochemistry. Results Our results showed that positive cells for both markers were present in all stages of tooth development, and the number of positive cells increased with the progression of this process. Cells of epithelial and ectomesenchymal origin were positive for CD146, and the expression of p75NTR was mainly detected in the dental papilla and dental follicle. In the postnatal group, dental pulp cells were positive for CD146, and the reduced enamel epithelium and the oral mucosa epithelium showed immunostaining for p75NTR. Conclusions These results suggest that the staining pattern of CD146 and p75NTR underwent temporal and spatial changes during odontogenesis and both markers were expressed by epithelial and mesenchymal cell types, which is relevant due to the significance of the epithelial-ectomesenchymal interactions in tooth development.